Crosstalk of Phosphorylation and Arginine Methylation in Disordered SRGG Repeats of Saccharomycescerevisiae Fibrillarin and Its Association with Nucleolar Localization. Issue 2 (17th January 2020) - Smith, Daniela-Lee; Erce, Melissa A.; Lai, Yu-Wen; Tomasetig, Florence; Hart-Smith, Gene; Hamey, Joshua J.; Wilkins, Marc R.
Abstract: Crosstalk exists when two or more post-translational modifications, nearby in sequence or 3D space, affect each other or a protein's interactions. Saccharomyces cerevisiae protein Npl3p has six repeats of sequence SRGG, in a disordered domain, which can carry arginine methylation and serine phosphorylation. Crosstalk of the modifications controls Npl3p interactions with nuclear import, export, and other proteins. Here, we asked whether repeated SRGG motifs existed in other S. cerevisiae proteins and whether they serve a related function. Two other proteins had multiple SRGG motifs: Nop1p (fibrillarin) and Gar1p, both nucleolar proteins, which had nine and four motifs, respectively. For Nop1p, we first showed it to be extensively methylated in vivo. We then showed that the Nop1p SRGG motif is subjected to methylation by Hmt1p, phosphorylation by Sky1p, and Glc7p dephosphorylation and that there is crosstalk whereby phosphorylation blocks methylation. This is consistent with our recent motif analysis of Hmt1p, which revealed a negative specificity for acidic residues at −1 and −2 positions. On knockout of HMT1, Nop1p-GFP localization was not typically nucleolar. Conditional two-hybrid analysis, of Nop1p with C/D box small ribonuclear proteins Nop56p and Nop58p, suggested this may be associated with decreased protein-protein interactions on loss of arginine methylation. The effect of SRGG phosphorylation on the interactions of Nop1p remains unknown yet was predicted to cause a structural disorder-to-order transition in the Nop1p N-terminal domain. The SRGG motif is one of very few examples of modification crosstalk that has related functions in multiple proteins from the same species. Graphical abstract: Image 1 Highlights: SRGG repeats exist in three nuclear proteins yet any related function was unknown. Nop1p is methylated by Hmt1p, phosphorylated by Sky1p, and dephosphorylated by Glc7p. Methylation and phosphorylation crosstalk, and methylation alters Nop1p interactions. Loss of methylation of Nop1p leads to atypical nucleolar localization. Phosphorylated SRGGs may modulate interactions via disorder to order transitions.